2012
DOI: 10.1590/s0104-07072012000300023
|View full text |Cite
|
Sign up to set email alerts
|

Reflexões acerca da integralidade nas reformas sanitária e agrária

Abstract: This reflective essay aimed to discuss agrarian and healthcare reforms from the perspective of the integrality of healthcare delivered to settlement families. Through this study, we determined that both the agrarian and healthcare reforms were intended, from their conception, to reduce social injustice, achieving the integrality and well-being of individuals and their families, whether in the context of agrarian reform, focused on landless individuals and their families, or in the context of healthcare reform,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
2
0
4
Order By: Relevance
“…20 This fact "is currently a challenge for integral care with organized labor, traditionally, in an extremely installments, with difficulty also to the universal." 21 In one study, 22 it was found that the FHS has allowed some progress in health care, but it is necessary to redirect the actions to be taken to achieve the transformation of the care model, with the effective involvement of users to ensure their needs, proposing an opening horizons to conquer the right to guarantee a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…20 This fact "is currently a challenge for integral care with organized labor, traditionally, in an extremely installments, with difficulty also to the universal." 21 In one study, 22 it was found that the FHS has allowed some progress in health care, but it is necessary to redirect the actions to be taken to achieve the transformation of the care model, with the effective involvement of users to ensure their needs, proposing an opening horizons to conquer the right to guarantee a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Levando em consideração os índices negativos de saúde das populações do campo e a carência de políticas públicas voltadas para esse segmento, a XII Conferência Nacional de Saúde em 2004 apontou como um dos principais desafi os do SUS a garantia do acesso ao sistema de saúde pela população rural (Bergamaschi, Teles, Souza, & Nakatami, 2012). Nesse caminho o Ministério da Saúde instituiu o Grupo da Terra, que trabalhou na elaboração da Política Nacional de Saúde Integral das Populações do Campo das Florestas e das Águas (PNSIPCFA) publicada no ano de 2011, e que busca levar em conta as especifi cidades das diferentes populações rurais brasileira visando o acesso integral e universal à saúde, além de introduzir nos programas de saúde já existentes as necessidades específi cas em saúde dessas populações.…”
Section: Cuidado Psicossocial Em Saúde Mental Em Contextos Rurais: Atunclassified
“…Taking into account the negative health rates of rural populations and the lack of public policies targeting them, the XII National Health Conference in 2004 identifi ed as one of the main challenges of SUS ensuring access to the health care system for such populations (Bergamaschi, Teles, Souza, & Nakatami, 2012). The Brazilian Ministry of Health created then the Land Working Group, which elaborated the National Comprehensive Health Care Policy for Rural, Forest and Water Populations (PNSIPCFA), introduced in 2011.…”
Section: Psychosocial and Mental Health Care In Rural Environments: Amentioning
confidence: 99%